Proteomic and Glucosinolate Profiling of Rapeseed Isolates from Meals Produced by Different Oil Extraction Processes. Issue 4 (14th September 2016) - Raikos, Vassilios; Neacsu, Madalina; Duthie, Garry; Nicol, Fergus; Reid, Martin; Cantlay, Louise L.; Ranawana, Viren
Abstract: The proteomes and glucosinolate content of two commercial rapeseed meals produced by cold‐pressing and pre‐press solvent extraction were investigated with the aim of identifying process‐related differences between them. One‐dimensional protein electrophoresis of the meals and their corresponding protein isolates revealed similarities in protein band distribution between cold‐pressed and pre‐press solvent extracted samples. Two‐dimensional protein electrophoresis coupled with mass spectrometry confirmed that the seed storage protein cruciferin was the major protein in both meals either intact or in the form of α‐ and β‐polypeptide subunits. HPLC analysis indicated that cold‐press meals contained significantly higher amounts of glucosinolates than the solvent‐extracted meals. Progoitrin was the main glucosinolate detected irrespective of the processing method used for extraction and leveled to 2.52 and 1.25 g/kg for cold‐pressed and solvent‐extracted meal, respectively. Furthermore, glucosinolate‐free protein isolates were prepared from this by‐product of the oil production industry. Practical Applications: The rapeseed meal of Brassica origin is a good source of protein but glucosinolate content limits its potential applications to animal feed. It is accepted that the oil production method can affect the nutritional composition of the meal produced because of the varying oil extraction conditions. In this study, significant differences were detected between the amounts of glucosinolate in cold‐pressed and solvent‐extracted meals, whereas protein content remained relatively unaffected. The protein isolates prepared from rapeseed meals were free of glucosinolates regardless of the extraction method. The findings of this study provide preliminary nutritional information of rapeseed protein isolate for potential applications as a food ingredient for animal and human consumption.